Understanding of Education Management and Tendencies of Its Development in Contemporary Educational Science Abroad - Želvys, Rimantas (Acta Paedagogica Vilnensia, 1996)
Education management is a relatively new brand of education not only in Lithuania, but in other countries as well The article reveals a short history of managerial science and discusses problems of defining management. Differences between the notions of management and administration are pointed out. The article also discusses the possibilities of managerial development in education, as well as arising problems and doubts. The specificity of educational institutions is usually pointed out as one of the main objections against using managerial principles at schools. Another problem, discussed in the article, is whether management has its own theoretical basis and whether being a manager is a profession. The final part of the article is aimed at the contents of studies of education management.